Fit an architects manifesto - Geddes, Robert (Princeton University Press, 2012)
Fit is a book about architecture and society that seeks to fundamentally change how architects and the public think about the task of design. Distinguished architect and urbanist Robert Geddes argues that buildings, landscapes, and cities should be designed to fit: fit the purpose, fit the place, fit future possibilities. Fit replaces old paradigms, such as form follows function, and less is more, by recognizing that the relationship between architecture and society is a true dialogue--dynamic, complex, and, if carried out with knowledge and skill, richly rewarding.